Improved two-dimensional cracked finite element for crack fault diagnosis - Kalanad, Aysha; Rao, B. N. (Computer Assisted Methods in Engineering and Science; Vol 19 No 3 (2012), 2017)
In this paper the two-dimensional finite element with an embedded edge crack proposed by Potirniche et al. (2008) is improved further for crack depth ratios ranging up to 0.9 and for predicting the natural frequency of a cracked beam more accurately. The element is implemented in the commercial finite element code ABAQUS as user element subroutine. The accuracy of the proposed improved cracked element is verified by comparing the predicted, first natural frequency with available experimental data. Subsequently, a methodology to detect the crack's location and size in conjunction with the proposed improved cracked element is also presented.